Historical experience of CSTO member states to organize and conduct joint operations in the information area - Olga Gapeyeva (Cхід, 2017)
Information security is a component of the state national security. In this regard, the urgent issue today is to ensure the security of state information resources, protection of vital interests of society in the information sphere.